Complex dynamics in psychosocial work with unaccompanied minor refugees with uncertain future prospects: A case study. (9th September 2020) - Hettich, Nora; Meurs, Patrick
Abstract: This case study explores the arriving process of an unaccompanied minor refugee in Germany and his perception of the psychosocial support he received. The aim is to elaborate possibilities to support refugee adolescents' arrival processes adequately. Two interviews—theme‐centered and narrative—were conducted and afterwards examined by a group of five researchers who used experts' validation as the analyzing tool. Four main dimensions were identified contributing to the complex dynamics in psychosocial work with unaccompanied minor refugees: (a) the distinct need for self‐determination and idealization, (b) the fight for state recognition as a legal refugee, (c) the attempt of achieving recognition by the society, and (d) the inability of building trusting and affective relationships with friends and caregivers in the host country. Thus, professionals working with unaccompanied minor refugees need to consider the adolescents' demand for self‐determination and perceive idealization not only as a defense mechanism but also as a coping strategy to survive in an unpredictable environment. Being a reliable object that can be used by the adolescent can help to establish a trusting basis for the relationship. This case study indicates that approaches of psychosocial support with unaccompanied minor refugees need to acknowledge and work with the interrelation between the inner world and the external reality of refugee adolescents.